The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1002/jpln.200900062
|View full text |Cite
|
Sign up to set email alerts
|

Soil‐organic‐matter stability in sandy cropland soils is related to land‐use history

Abstract: Sandy cropland soils in NW Europe were found to contain unusually high organic-carbon (OC) levels, and a link with their land-use history has been suggested. This study's aim was to assess the discriminating power of physical and chemical fractionation procedures to yield information on soil-organic-matter (OM) stability for these soils. In relict-and cultivated-heathland soils, much higher proportions of 6% NaOCl treatment-resistant but 10% HF-soluble OC (MOC) and N (32.2% and 29.9%) were measured compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…These differences were also confirmed for a larger soil set studied by Sleutel et al (2010). Differences in N content ofthe physical fractions were smaller and insignificant.…”
Section: Organic Carbon and Nitrogen Distribution Over Isolated Size supporting
confidence: 71%
See 2 more Smart Citations
“…These differences were also confirmed for a larger soil set studied by Sleutel et al (2010). Differences in N content ofthe physical fractions were smaller and insignificant.…”
Section: Organic Carbon and Nitrogen Distribution Over Isolated Size supporting
confidence: 71%
“…Both were commonly practiced over centuries in Northwest Europe from Schleswig-Holstein to Belgium (Blume and Leinweber, 2004). Studies employing incubation experiments, physical and chemical fractionation methods (Springob and Kirchmann, 2002;Sleutel et al, 2010) and detailed spectroscopic characterizations (Sleutel et al, 2008) have confirmed both the similarity in soil OM stability of relict and cultivated heathlands on the one hand, and the lower stability of soil OM in sandy cropland soils without this historical land use on the other. Specifically, lipids, sterols and to a lesser extent N-containing compounds were selectively preserved from previous heathland land-use (Sleutel et al, 2008).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Within the here studied loess soils, humus class became as important as the clay contents. This did not apply to sandy soils, probably due to relatively high amounts of relatively stable SOM in podzolized sandy arable soils with very low clay contents (Sleutel et al 2010;Springob and Kirchmann 2002).…”
Section: Resultsmentioning
confidence: 98%
“…Corroborating our findings, in the Cerrado region, a 49 % difference in the clay content between two soils was responsible for a 46 % reduction in soil organic carbon (SOC) losses when the native vegetation was converted to conventional tillage systems (Dieckow et al, 2009). The lower aggregation capacity, specific surface, and charge density in sandy soils make soil C biochemistry properties of fundamental importance to SOC preservation over time (Sleutel et al, 2010). Remarkably, after three years of residue removal, δ 13 C-POM was less negative than initially recorded in the West region (Table 2), indicating a selective preservation of C derived from C 4 plants.…”
Section: Discussionmentioning
confidence: 96%